The BBC and the Development of Anglophone Caribbean Literature, 1943-1958 - Griffith, Glyne A.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book is the first to analyse how BBC radio presented Anglophone Caribbean literature and in turn aided and influenced the shape of imaginative writing in the region. Glyne A. Griffith examines Caribbean Voices broadcasts to the region over a fifteen-year period and reveals that though the program's funding was colonial in orientation, the content and form were antithetical to the very colonial enterprise that had brought the program into existence. Part literary history and part literary biography, this study fills a gap in the narrative of the region's literary history. .
Introduction -- The Genesis of Caribbean Voices: People and Policies -- The Critics' Circle -- Caribbean Voices and Competing Visions of Post-Colonial Community -- A Sustaining Epistolarly Community -- The Naipaul / Mittelholzer Years: 1954-58 -- Afterword. .
Keywords: Comparative literature; Literature, Modern-20th century; United States-Study and teaching; British Culture; American Culture